Intake of a Mediterranean Diet Reduces Atherogenic Lipid Profiles but the Effect Is Diminished by Daily Egg Intake. (7th June 2021) - Picklo, Matthew; Rust, Bret; Yeater, Kathleen; Raatz, Susan
Abstract: Objectives: A Mediterranean diet (Med Diet) decreases atherogenic lipoproteins and cardiovascular disease (CVD) risk. It is unknown how high cholesterol intake within a Med Diet will affect these parameters. The objective of this project was to evaluate the daily inclusion of whole eggs, a high cholesterol food, in the Med Diet on lipid and lipoprotein profiles. Methods: Overweight to obese men (8) and women (25) were recruited into a randomized, cross-over designed, controlled feeding study evaluating three isocaloric test diets: a) Control –average American diet from What We Eat in America, b) Med Diet, and c) Med Diet plus whole, fresh eggs (1 whole egg/1000 kcal; Med Diet + Egg). The Control and Med Diet contained egg substitute. Participants were directed to consume only those foods provided during each 4-week diet treatment period. Each treatment period was separated by > 4-week washout period. Fasting blood was taken pre- and post-treatment for determination of lipid concentrations, lipoprotein particle size and number. Results: Intake of the Control and Med Diet, but not the Med Diet + Egg, decreased (time effect, P < 0.05) total cholesterol and low density lipoprotein (LDL) concentrations, but an overall diet treatment effect did not occur. Med Diet, but not Control or Med Diet + Egg, reduced (time effect, P < 0.05) triglyceride concentrations, but an overall treatment effect did not occur. Particle numbers ( P < 0.05) were reduced ( P < 0.05) for intermediate density lipoprotein (26%) and total LDL (8%) by Med Diet intake but not by the other diets, and an overall treatment effect was not observed. Very low density lipoprotein size was reduced ( P < 0.05) by Med Diet intake and an overall treatment effect occurred ( P = 0.04). Variability in responses was assessed by hierarchical clustering heatmap analysis of blood lipid responses. Three main categories of responses types were present but not defined by dietary treatment. Conclusions: Daily intake of a Mediterranean diet meal pattern or an average American diet without whole eggs reduced blood lipid and/or lipoprotein concentrations associated with CVD risk; addition of daily egg intake blunted these reductions. However, the variability in the study population responses warrants further nutrigenomic exploration. Funding Sources: USDA-ARS 3062-53000-001-00D and the American Egg Board.